Agriculture as a Determinant of Zambian Economic Sustainability - (:unkn) unknown (MDPI, 2020)
For several years, the Zambian economy relied on the mining sector, which has been affected by fluctuations in commodity prices. The new century enhanced the calls for economic diversification, with the agricultural, manufacturing, and services sectors amongst those pronounced. This article focused on the role of agriculture in supporting the economy, particularly, the effect of agriculture on economic growth. The data analyzed was reviewed for the period 1983-2017. The ARDL Bounds Test was applied in order to meet the said objectives. The ECM results suggest that agriculture, manufacturing, services, and mining converge to an equilibrium and affect economic growth at the speed of adjustment of 90.6%, with the effect from agriculture, mining, and services being significant. The impact of agriculture on economic growth was significant in both the short-run and long-run, with coefficient unit effects of 0.428 and 0.342, respectively. The effects are strong because more than two-thirds of the rural population rely on farming, and agriculture has stood as a catalyst for food security. For the effect of agriculture to be much more profound, farmers must be supported with adequate infrastructure, accessibility to markets, farming inputs, better irrigation techniques, which would address the problem of reliance on rain, all of which were inconsistent in the last decade. Additionally, governments must ensure the institutionalization of food processing industries which add more value to the national income.
Keywords: agriculture; economic sustainability; economic growth; ARDL bounds test; Zambia; TIME-SERIES; UNIT-ROOT; GROWTH; COINTEGRATION